Clinical Characteristics and Results of Transungual Excision of Subungual Glomus Tumor - Pandey, Suresh (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Glomus tumor is rare and subungual location of the distal phalanx is the most common site. Surgical excision is the mainstay of treatment to relieve the symptoms. The objective of this study was to analyze the clinical characteristics and result of transungual excision of the tumor. Methods A retrospective cross sectional study of was conducted among 15 cases of subungual glomus tumors operated with transungual excision over 8 years period in the department of Orthopedics. The clinical and demographic characteristics were noted from the case record. The outcome variables were assessed from case records, OPD visits, and telephone interviews and the results analyzed were pain relief, postoperative recurrence, nail deformity, and patient satisfaction. Data was analyzed by using descriptive statistical tools in SPSS-20. Results The mean age of the patients was 32.6 years with the mean duration of symptoms 1.8 years. The mean tumor size was 3.4 mm. Pain and pinpoint tenderness were present in all 15 cases and positive cold sensitivity test and positive Hildreth’s test in 13 (86.7%) and 10 (66.7%) cases respectively. All cases had complete relief of pain within 2 weeks of the operation. There was no case of recurrence and nail deformity till a minimum of 1 year of follow up. Conclusions The diagnostic clinical triad of pain, point tenderness, and cold sensitivity are the most common findings. The transungual excision of the tumor can give rise to excellent results with complete relief of pain in all cases with no recurrence or nail deformity.